A perspective-evidence link diagram activity: focus on COVID-19. (26th January 2022) - Durak, Benzegul; Arslan, Harika Ozge
Abstract: During the unprecedented and rapid spread of the coronavirus disease-2019 (COVID-19) around the World, students have been concerned about the disease as much as the rest of the global community. As a real-world problem, the COVID-19 pandemic with many different debatable facets has social and scientific components, impacts society, and shows socioscientific issue characteristics. The pandemic blew up a debate about wearing or not wearing a face mask against infection and occupied the world agenda for nearly six months. After the World Health Organization (WHO) supports wearing face masks, a new debate on whether to wear fabric or a medical mask to protect public health started. Depending on that debate, a Perspective-Evidence Link diagram activity is designed for high school students and presented in this paper. The designed activity uses two different perspectives related to that debate and texts providing pieces of evidence for these perspectives. Students are expected to make different types of connections indicating the support/contradiction/irrelevancy of these texts to each perspective while explaining their reasons for selecting different connection types. In addition to explaining the details of how to use the designed COVID-19-Perspective-Evidence Link diagram as online activity, this paper makes recommendations for classroom usage to help teachers use it in a productive manner.